Malay, Islam, Beraja and The [Islamic] Educational Philosophy in Brunei Darussalam - Thoriquttyas, Titis; Nasih, Ahmad Munjin; Sultoni, Achmad; Yani, Achmad (EDUKASIA, 2021)
The ideology of Brunei Darussalam contributes in shaping the [Islamic] Education system. Politically, Brunei applies the concept of Malay, Islam, Beraja (MIB) as an ideological basis. This research is oriented to two main discussions. First is the historical trajectory of MIB in Brunei and its relation to the education system. The second is the dimension of educational philosophy and Islamic education philosophy in Brunei by drawing its relation to the MIB. This research uses a qualitative-naturalistic approach. This research was conducted in Brunei, October 2019. Data was collected through interviews, focus group discussions (FGD), observation, document and literature studies. In data collection, this research involved academics from Kolej Universiti Perguruan Ugama Seri Begawan (KUPU) and Sultan Sharif Ali Islamic University (UNISSA). The findings show that the MIB is related to the model perennialism and progressivism. However, from Islamic education philosophy, MIB gives a traditionalist style to the mazhabi and modernist education system.